Gendered (SDG5) and other perspectives on COVID-19 vaccination status: a focus on South Africa's Limpopo province - Nhamo, Godwell; Maoela, Malebajoa Anicia (Frontiers in Global Women's Health, 2024)
One of the key issues embedded in the 2030 Agenda for Sustainable Development is the need for disaggregated data. Given the nature of the Coronavirus disease 2019 , studies on such should respond to this call. This paper investigates gendered and other perspectives on COVID-19 vaccination status in South Africa's Limpopo Province. The work utilises a household survey (n=4,571), data from Our World in Data and Johns Hopkins University, as well as policy documents and academic literature. The findings are that the government moved away from a goal to attain 67% herd immunity, to the containment strategy. While the country attained 35% of population fully vaccinated, the current study reveals 72.84% of the respondents fully vaccinated in Limpopo (including those receiving a booster). Noteworthy findings include 7.1% of the respondents reporting partial vaccination and 19.8% expressing vaccine hesitancy. Gender differences were significant, with females exhibiting higher vaccination rates than males, and age-related variations were observed, particularly among the youngest participants. Further analysis stratified by gender and age groups unveiled substantial disparities, emphasizing the need for targeted interventions. Additionally, the study highlights patterns in COVID-19 vaccine uptake based on education levels, with higher education associating with increased vaccination rates. Significant gender-based differences in vaccine uptake across education levels indicate potential areas for focused public health efforts. The findings emphasise the complexity of factors influencing vaccination behaviour, providing valuable insights for policymakers, public health practitioners, and researchers aiming to enhance vaccine uptake and address disparities in diverse demographic groups.